2017
DOI: 10.1038/s41598-017-04178-7
|View full text |Cite
|
Sign up to set email alerts
|

Integrating genome and transcriptome profiling for elucidating the mechanism of muscle growth and lipid deposition in Pekin ducks

Abstract: Muscle growth and lipid deposition are co-ordinately regulated processes. Cherry Valley Pekin duck is a lean-type duck breed with high growth rate, whereas the native Pekin duck of China has high lipid deposition. Phenotypic analysis showed that native Pekin ducks have smaller fibre diameter and larger density in the breast muscle at 3 weeks of age and higher intramuscular fat content at 6 weeks of age than those in Cherry Valley Pekin ducks. We detected 17 positively selected genes (PSGs) by comparing genes m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…In ducks, muscle growth and lipid deposition are two important features representing the main breeding objectives. Previously, 10 and 11 candidate genes related to duck muscle growth and lipid deposition have been reported [48]. However, the selected genes identified in this study do not overlapped with these previously reported candidate genes.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…In ducks, muscle growth and lipid deposition are two important features representing the main breeding objectives. Previously, 10 and 11 candidate genes related to duck muscle growth and lipid deposition have been reported [48]. However, the selected genes identified in this study do not overlapped with these previously reported candidate genes.…”
Section: Resultsmentioning
confidence: 54%
“…However, the selected genes identified in this study do not overlapped with these previously reported candidate genes. As the previous study was performed using different duck breeds (a native Pekin duck with higher fat content and a Pekin duck bred crossbred with a native British duck breed with higher lean meat percentage and intramuscular fat content) [48,49], the differences observed between these studies suggest differential adaption mechanisms underlie the same phenotypic changes observed across distinct duck populations.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in glucose and lipid metabolism between wild and domesticated animals due to directional selection were also observed in pigs [25] and chickens [3]. Enpp3 and Prkar2b were identi ed as the targets of selection during the domestication of Pekin ducks and other indigenous Chinese ducks [26,27].…”
Section: Selection For Domesticationmentioning
confidence: 97%
“…DST ( dystonin ) has been associated with slower bone healing in sheep (JĂ€ger et al ) and with feed efficiency, muscle structure and carcass length in pigs (Damon et al ; Liu et al ; Gondret et al ). MYO7B ( myosin VIIB ) in ducks is associated with muscle growth and with the deposition of lipids, and is a gene that has undergone positive selection (Wang et al ). ITGA4 ( integrin subunit alpha 4 ) has been identified as one of the candidate genes responsible for differences in residual feed intake (Hou et al ; Salleh et al ), and it is also associated with fetal myostatin loss‐of‐function in bovine muscle (Cassar‐Malek et al ).…”
Section: Snps Significantly Associated With Ashidan Yak Body Weight (mentioning
confidence: 99%